Improving occupational safety through the implementation of a management system based on ISO 45001 in a primary forest processing plant – Puno, Peru (International Journal of Occupational Safety and Health, 2026)
Introduction: This study assessed the impact of implementing an Occupational Health and Safety Management System (OHSMS) based on ISO 45001:2018 at Corporación Caliz S.A.C.'s primary forest processing facility in Puno, Peru— an industrial site with high occupational risks. The objective was to evaluate whether the structured implementation of this international standard could significantly enhance workplace safety culture and operational risk management.Methods: A quasi-experimental design with pre-test and post-test measurements was applied to a cohort of 37 employees. Data collection involved a 22-item structured survey mapped to the seven core clauses of ISO 45001, the IPERC matrix for risk assessment, and direct on-site observations. The Shapiro–Wilk and Wilcoxon signed-rank tests were used for statistical analysis.Results: Post-intervention results showed significant improvements (p < 0.001) across all ISO 45001 clauses. Safety perception increased by 45%, leadership and worker participation by 41%, and proper use of personal protective equipment by 52%. The significant progress was observed in Clause 7 (Support, Z = 4.99), Clause 6 (Planning, Z = 4.47), and Clause 9 (Performance Evaluation, Z = 4.55), confirming the strengthening of the preventive culture and the improvement of risk control mechanisms.Conclusion: Implementing ISO 45001:2018 can produce measurable advancements. It led to significant improvements in preventive culture, risk mitigation, and regulatory compliance in hazardous industrial settings. It led to significant improvements in preventive culture, risk mitigation, and regulatory compliance in hazardous industrial settings within high-risk industries. These findings provide empirical support for adopting the standard and highlight the importance of sustained corrective action and continuous monitoring. Future longitudinal and cross-sectoral studies are recommended to evaluate the long-term impact and integration with other management systems.